Radiological safety assessment of sugar consumption in South Africa—a study of 226Ra, 228Ra, and 40K levels - John, Samuel Odumu Ogana; Olukotun, Stephen Friday; Radebe, Moses Mpofana; Mathuthu, Manny (Frontiers in Public Health, 2025)
Human exposure to natural radionuclides in the environment primarily occurs through ingestion of foodstuffs, highlighting the importance of continuous monitoring of radionuclide levels in foodstuffs by ensuring consumer safety and compliance with regulatory standards. Using gamma spectrometry, this study investigates activity concentration levels of 226Ra, 228Ra, and 40K, and associated radiological health risks, in 14 commonly available sugar brands in South Africa. The activity concentration levels of these natural radionuclides ranged from 2.01 ± 0.13 to 7.93 ± 0.34 Bq/kg for 226Ra, 2.90 ± 0.10 to 7.09 ± 0.32 Bq/kg for 228Ra, and 209.40 ± 4.79 to 453.20 ± 10.49 Bq/kg for 40K. The respective mean values were 3.83 ± 0.21, 2.90 ± 0.21, and 320.26 ± 7.41 Bq/kg, with brown sugar having lower values than with white sugar. Annual effective ingestion dose from intake of 226Ra, 228Ra, and 40K, for infants (1–2 years), children (7–12 years), and adults (>17 years) ranged from 0.28 to 0.69, 0.32 to 0.82, and 0.12 to 0.30 mSv/year, respectively, and the respective mean values are 0.40 ± 0.11, 0.45 ± 0.14, and 0.17 ± 0.05 mSv/year. 228Ra contributed the largest proportion to ingestion dose (46–67%), indicating potential radiation risk to bones. Lifetime cancer risk ranged from 1.25 × 10−8 to 4.95 × 10−8 for 226Ra, 1.95 × 10−8 to 4.77 × 10−8 for 228Ra, and 5.53 × 10−7 to 1.19 × 10−6 for 40K, with a total mean of 8.96 × 10−7 ± 2.31 × 10−7. Total chronic daily intake due to 226Ra, 228Ra, and 40K ranged from 0.26 to 0.56 with a mean of 0.39 ± 0.10 (mg/kg-day). The activity concentration levels of the natural radionuclides are within the reference value while annual effective ingestion dose and lifetime cancer risks were below international permissible limits. This indicates that sugar in South Africa is radiologically safe and does not pose significant radiological health risks. In this study, the measured activity levels are comparable to those reported in other similar studies. This baseline study highlights the importance of continuous monitoring of radionuclide levels in foodstuffs, ensuring consumer safety, compliance with regulatory standards, and contributing to ongoing discussions on radiological health risks associated with dietary habits. Public health initiatives could consider offering guidelines for safe levels of consumables such as sugar, especially among vulnerable populations such as children.